THE INFLUENCE OF HEALTH EDUCATING IN PREVENTING COVID-19 TOWARDS INCREASING THE FREGNANT WOMEN’S KNOWLEDGE AND BEHAVIOR DURING THE PANDEMIC - Rahayu, Dedeh Sri; Ambarsari, Wulan Novika (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
COVID-19 has increased the number of victims and property losses. This research aims to determine the effect of health education on preventing COVID-19 towards increasing the knowledge and behavior of pregnant women during the pandemic. This research uses an experimental design with a pre-experimental method and a one-group pre-post-test design. The number of pregnant women respondents in the working area of the Cibeber and North Cimahi Health Center was 132 people. Result: Most of the knowledge of pregnant women before being given health education was sufficient, but afterward most of it was good. Pre-health education behavior at the Cibeber and North Cimahi Community Health Centers is primarily deficient. However, post-health education behavior at the Cibeber Community Health Center is primarily deficient. At the North Cimahi Community Health Center; the results are 50% deficient and 50% good. The influence of Health Education on the knowledge and behavior of pregnant women at the Cibeber and North Cimahi Community Health Centers using Paired samples correlations obtained p=0.0000 < α (0.05), so there is an influence. However, in comparison of the influence of health education on the knowledge among pregnant women, there are differensces between the two. A comparison of the influence of health education on the behavior of pregnant women in Cibeber and North Cimahi resulted in p = 0.00 < α (0.05), than there is influence. Conclusion: Health education influences the knowledge and behavior of pregnant women in preventing COVID-19, however, there are differences in comparing the influence of health education. Towards increasing knowledge in Cibeber and North Cimahi. Suggetion: Health education regarding prevention of disease transmission, it is carried out continuously and on a schedule to the community. Keywords: Covid-19, pregnant mother, health education, knowledge, behavior.